What is a Topological Hermeneutics? From Logical Hermeneutics to Topological Hermeneutics, that is, about Certain Methods of Analytical Philosophy - Kaczmarek, Janusz (Analiza, racjonalność, filozofia religii: Księga jubileuszowa dedykowana Profesorowi Ryszardowi Kleszczowi. Nr 6 (2020), 2020)
In the paper I proposed a new analytical method, which I called topological hermeneutics. In Chapters 2 and 3 I recalled the well-known methods of analytical philosophy, namely: the method of logical hermeneutics proposed by Wolniewicz in the 1980s and the earlier method, i.e. the paraphrase method given by Ajdukiewicz in the 1930s. In the next point (in Chapter 4) I proposed and explained what the interpretation and modelling within the topological ontology is. Here I pointed out some solutions on the example of Lowe’s four-category ontology and explained the meaning of formal and interpretative theorems, which – in my opinion – are the basis of the formal ontology methodology in this topological one.  Praca została wykonana przy wsparciu Narodowego Centrum Nauki, projekt” Atom. Substancja. System. Badania z zakresu ontologii topologicznej” (nr 2017/27//B/HS1/02830).